Influências da neurociência cognitiva no ensino de química : como os conhecimentos sobre atenção seletiva poderiam auxiliar na aprendizagem das funções orgânicas? - Menezes, Thiago de Carvalho (2022)
The present study aimed to investigate the effects that the application of a didactic game based on the constructs of Cognitive Neuroscience, specifically on executive function selective attention, has on the neurocognitive adaptations of teenage high school students in relation to learning the content Organic Functions (FO). Thus, the investigation on screen was conducted under the methodological perspective of Classic Didactic Engineering (EDC) proposed by Artigue (1998), which initially resulted in the previous analysis, conception and a priori analysis of a Didactic Sequence (SD) based on the fundamentals of Cognitive Neuroscience. Based on this understanding, theoretical contributions were sought from authors such as Luria (1979, 1980), Kandel (1991), Gazzaniga (2006), Lent (2008, 2010) and Sternberg (2008, 2010), in order to study the characteristics of the cognitive function attention, as well as, the internal and external influences for its request. Indeed, in the educational context, inspiration was sought in the research developed by Cosenza and Guerra (2011) about factors such as “perception”, “memory” and “attention” in school learning. In this sense, a historical and epistemological survey was carried out in order to identify the obstacles that are possibly associated with conceptual problems common to students, including: theory contrary to Paraceltist constructs (OB1), theories adverse to the conception that the atom was understood as a fundamental entity of matter (OB2), difficulty in representing the structures of compounds from empirical data (OB3), among others. From this perspective, it could also be noted that the understanding of the FO content, on the part of students, has been a difficult task in High School, as it is possible to notice the absence of theoretical and methodological investments that provide the applicability of these materials teaching activities in the classroom context. Finally, it is also highlighted that the structuring of the didactic sequence was based on the following steps: the field of investigation and the target audience, the revelation of paths in solving issues, the determination of previous chemical knowledge linked and supposedly available and the anticipation of possible obstacles presented by the students during the resolution of the questions, considering the time available to carry out the research, the availability and interest of the study volunteers, among others. Indeed, the resources used for data collection were field diaries for daily records and tests. The research results showed that the association of facts and characteristics of Organic Functions with the daily lives of students, as well as the use of multisensory resources, provided greater commitment by students and facilitated the consolidation and recall of memories about OC. The making of molecular structures through the molecular kit provided for the perception and correction of errors arising from the representations of the students' structural formulas.